Determinasi Tingkat Penyaluran Kredit Pemilikan Rumah (Periode Setelah Kebijakan Loan to Value) - Titia Dwianingrum (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to find out how the impact of loan to value policy on bank value in determining the amount of mortgage loans which are distributed, as well as knowing what is the dominant variable affecting the bank in determining the amount of the mortgage loan portfolio. In addition, during the years 2010 - 2014 the number of mortgage loans which are distributed increased continuously and decreased since 2013. The method used in this research is to use panel data regression which is a combination of the data time series and cross section. Sample of this research choosen by purposive sampling technique. This study resulted that after the loan to value policy, only DPK and LDR variable are significant affected mortgage lending and have positive coefficient, while the variable CAR, NPLs, ROA, BOPO, and BI rate has no significant effect on mortgage lending.Keywords: Mortgage Lending, Loan to Value, DPK, CAR, NPLs, ROA, LDR, BOPO, BI Rate